THE HIDDEN STRUCTURE OF VOLUNTARY TURNOVER THEORY EVOLUTION: A SPAR-4-SLR META-THEORETICAL ANALYSIS - Krisna Andita; Hady Siti Hadijah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to construct an integrated structural synthesis of the evolution of voluntary turnover (VTO) theory, mapping both its chronological development and the conceptual genealogy linking its theories, together with the variables derived from each theory in the most recent phase. The method is a systematic literature review applying the SPAR-4-SLR protocol combined with the TCM-ADO framework, drawing on high-quality, peer-reviewed articles indexed in Scopus and examined through content analysis. The results show that VTO theory has evolved along several interconnected pathways, from a foundational early-mobility era through attitudinal, adaptation, and dynamic-cognitive eras to a recent alternative-pathway era; theories develop both independently and through cross-era influence, and their derived variables relate to turnover in increasing, decreasing, and curvilinear ways. The synthesis offers conceptual clarity for researchers and a genealogical map to guide retention strategy and future VTO research.